CSR PRACTICES BY BUSINESESS IN ALBANIA. RESULTS OF A SURVEY - Cela, Miresi; Resmeliu, Dorina (European Scientific Journal, ESJ, 2015)
Corporate social responsibility has evolved over time. It is time for Albania to enter the European Union, and a path toward it is by being socially responsible. The main aim of this paper is to investigate corporate social responsibility practices from the perspective of businesses in Albania. At what extent is the knowledge of CSR concept among businesses employees, especially entrepreneurs and managers of the firms. At what extent are they engaged in CSR activities, how much they know about the benefits of the socially responsible behavior of enterprises. What are the barriers they face? A questionnaire was distributed to the businesses of the Central Albania Region. The survey results demonstrate that companies do engage in CSR activities, but only a limited number go beyond what is required by the law. There is much to be done, companies should integrate CSR in their strategic management. Major limitation of this research is the sample size, which limits the generalizing of the findings to the whole country.